Control of Omni-Directional Mecanum wheel mobile Robot and analysis of Artificial Muscle - Mohamedd Rizon, Mohamed Juhari, Prof Madya Dr.; Jefri Efendi, Mohd Salih; Mohammad Hanif, Abdul Hamid (Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 2009)
This paper presents the processes undertaken in the design and development of an intelligent omni-directional mobile robot using four custom-made mecanum wheels. The mecanum wheel developed consists of nine rollers made from delrin. All mecanum wheels are independently powered using four units of precisian gear DC motors and the wheel/motor assemblies were mounted directly to the robot chassis made using an aluminum frame. A four channel high power H-bridge using 2 units of LMD 18200 motor drivers IC circuit was design, built and interfaced to a BasicStamp (BS2) microcontroller board. Basic mobility algorithm using BasicStamp software was developed to test the basic mobility capabilities and test the qualitative view of the system's mobility performance. An experiment was set-up to analyze the motion characteristic of the mobile robot motion in Y-axis, X-axis and rotary motion. Data from the experiment will be used for mathematically model for mobile robot platform and speed controller modeling and design. Mecanum wheel mobile robot provides a convenient platform for further development in the mobile platform. The combination of mechanical design on the wheel and chassis, motion control and multiple input/output sensors allow the exploration of large number of control algorithm and software to be implemented to the robot for practical applications.